2018
DOI: 10.11613/bm.2018.030707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selected T cell subsets in peripheral blood after exhaustive effort among elite soccer players

Abstract: IntroductionPhysical exercise induces developing of naïve T lymphocyte subsets into polarised effector ones by immune system. The aim of the study was to examine the influence of exhaustive effort on the selected Th cell subsets and inflammation markers among soccer players.Materials and methodsFourteen soccer players aged 18 (16-21) years old performed the progressive efficiency test on mechanical treadmill. Th and Tc memory lymphocytes’ subsets and selected cytokine concentrations pre-exercise, post-exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 22 publications
10
47
3
Order By: Relevance
“…Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35]. The present study confirms that the immune response induced by the progressive effort is associated with the Th1 but not Th2 cell subset.…”
Section: Th Cell Subset Alterationssupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35]. The present study confirms that the immune response induced by the progressive effort is associated with the Th1 but not Th2 cell subset.…”
Section: Th Cell Subset Alterationssupporting
confidence: 83%
“…The antibodies cocktail contained: FITC-labelled interferon-gamma (clone B27), PE-labelled IL-17A (clone N49-653), PerCP-Cy5.5-labelled CD4 (clone SK3), and APC-labelled IL-4 (clone MP4-25D2). To measure Treg cell subsets, the Human Th17/Treg Phenotyping Kit (BD Pharmingen™, San Jose, CA, USA) were used, as described previously [20]. The antibodies cocktail contained: PElabelled IL-17A, PerCP-Cy5.5-labelled CD4, and Alexa Fluor1 647-labelled FoxP3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking the fact that WBC parameters (count and percentages of total WBC and their subpopulations) are the markers of general health status into account, the observed results of the present study may be considered as positive and confirming properly prescribed training loads and organism's adaptation to them. Our previous works revealed post-effort increase in WBC parameter values caused not so much by the dehydration but related to immunological response to performed exercise [58][59][60].…”
Section: The Impact Of the Training Program On Red And White Blood Cementioning
confidence: 95%